Overview of Potential Application of Pineapple Leaves Fibre Focusing on Moisture Damage - Mohd Fadil, Norhafizah; Mohd Ezree, (Recent Trends in Civil Engineering and Built Environment, 2022)
Asphalt pavement is exposed to extraordinary damage. In bituminous mixtures, numerous issues are expected to stripping of the cover from the aggregate The main goal of this research is to study modified asphalt mixture with pineapple fibres. This study is significant in evaluating pineapple leaves fibre potential in asphalt mixture based on physical, mechanical and chemical properties of pineapple leaves fibre. Besides, Marshall Stability and Moisture Susceptibility test of asphalt mixture’s performance with pineapple leaves fibre from previous study was also studied. Pineapple leaves fibre can be used to entirely or partially replace synthetic fibres in the construction of composite products for a variety of purposes. Pineapple leaves fibre has a density similar to other natural fibres, a high Young's modulus, and the best tensile strength among the related natural fibres. These characteristics make it excellent for use as a construction material. Laboratory experiment should be done for better result and acquire optimum percentage value of fibre content.